Robot-assisted laparoscopic pyeloplasty versus laparoscopic pyeloplasty for pelvi-ureteric junction obstruction in the paediatric population: a systematic review and meta-analysis. (March 2019) - Taktak, Samih; Llewellyn, Oliver; Aboelsoud, Mohamed; Hajibandeh, Shahab; Hajibandeh, Shahin
Background: Owing to the improved vision and instrument manipulation in robot-assisted procedures, we sought to evaluate the comparative outcomes of robot-assisted laparoscopic pyeloplasty (RALP) and laparoscopic pyeloplasty (LP) in a paediatric patients with pelvi-ureteric junction obstruction (PUJO). Methods: We conducted a systemic literature search of online sources, including PubMed, MEDLINE, EMBASE and Cochrane Central Register of Controlled Trials, and respective bibliographic reference lists. Success rate, operative time, hospital length of stay, postoperative complication rate and re-intervention rate were our primary outcomes. Combined overall effect sizes were calculated using fixed-effect or random-effects models. Results: We identified 14 observational studies reporting a total of 2254 paediatric patients with PUJO, who underwent LP ( n = 1021) or RALP ( n = 1233). Our analysis demonstrated that RALP was associated with a significantly higher success rate [odds ratio (OR) 2.51; 95% confidence interval (CI) 1.08–5.83, p = 0.03] and shorter length of hospital stay [mean difference (MD) −1.49; 95% CI −2.22 to −077; p < 0.0001] compared with LP. Moreover, nonsignificant reductions in postoperative complications (OR 0.61; 95% CI 0.36–1.02; p = 0.06) and re-intervention (OR 0.43; 95% CI 0.15–1.21; p = 0.11) were found in favour of RALP. There was no difference in procedure time between the two approaches (MD −0.15; 95% CI −30.22 to 29.93, p = 0.99). Conclusions: Our meta-analysis of observational studies demonstrated that RALP is safe and may have higher success rate compared with the more traditional laparoscopic approach in a paediatric population. Moreover, it may be associated with lower postoperative complications and re-intervention rates. Evidence from randomized trials is required.